'Ghostwriting': An Introduction to Ghost Stories by Women - Abao, Frances Jane P. (Review of Women's Studies; Vol 21 No 1 (2011): Review of Women's Studies Volume XXI, Number 1 (January-June 2011), 2011)
This essay identifies and describes significant topics of ghost stories by selected English and American women writers from the nineteenth century to the present day. It looks at how these writers have used the ghost story to explore common problematic experiences of women such as abusive relationships, troubled marriages, and sexual desire. As a non-realistic genre, the ghost story allows women writers to articulate, confront, and possibly come to terms with disturbing or subversive issues that may not be satisfactorily addressed through realistic fiction.